Research and application of new anti-floating anchor in anti-floating reinforcement of existing underground structures - Liu, Guohui; Jia, Pingsheng; Sun, Jianping; Jiang, Zongbao; Yang, Fan; Yang, Guorui; Shao, Guangbiao (Frontiers in Earth Science, 2024)
In recent years, due to the changing climate conditions and the continuous deepening of water resource conservation measures, the groundwater level in northern China has gradually risen, leading to the increasingly prominent issue of anti-floating in existing buildings and structures. The development and adoption of reliable antifloating reinforcement techniques for existing structures are crucial for ensuring the quality of such reinforcements. Therefore, focusing on the limitations of the anchor method for anti-floating reinforcement, this paper proposes a new type of anti-floating prestressed compression anchor that features a full-length anti-compressive steel pipe with a bearing body at the end and uses non-bonding tendons throughout its length. Firstly, the structural form of this pressure-type anchor is introduced; subsequently, combined with the results of on-site pull-out tests of the anchor, an analysis is conducted on the working principle, lateral resistance distribution, and internal force transfer mechanism of the new anti-floating anchor, and its load-bearing characteristics are elucidated. Finally, relying on actual anti-floating reinforcement projects and through numerical calculations, the changes in internal forces under different anti-floating conditions of existing structures reinforced with the new anchor compared to conventional anchors are contrasted. Research findings and engineering practice indicate that this new anti-floating anchor improves the mechanical performance of the grout body of the anchor, solves the water seepage problem at the anchor location of the waterproof slab, effectively suppresses cracking of the foundation waterproof slab after reinforcement, and enhances the anti-floating and durability of existing structures.